Editorial - Mathew, Thomas (Christ University Law Journal, 2021)
The Journal and Publication Society, School of Law, Christ University, takes pride in placing on record the fifth issue of its law journal. This issue of the Christ University Law Journal encompasses articles, case comments and legislative notes from diverse areas of law, which entails contemporary relevance. Contentious problems like access to justice of the disabled, recurrent and increasing spate of marital rapes, issues faced by street vendors who are trying to earn a living, employing of guerilla tactics in international arbitration and the significance of advance pricing agreements in the Indian taxation regime have been addressed in well researched articles. Complex legal questions have been discussed in acase comment on the conflicting provisions of the Indian Penal Code, 1860.